Fatigue flexural analysis of concrete beams reinforced with hybrid GFRP and steel bars. (15th November 2019) - Xu, Jiajing; Zhu, Peng; Ma, Zhongguo John; Qu, Wenjun
Highlights: Fatigue behaviors of concrete beams with hybrid GFRP bars and steel bars are studied. Analytical model with residual strain considered is proposed for fatigue prediction. Effects of effective reinforcement ratio and A f / A s are studied. Abstract: This paper presents fatigue behaviors of concrete beams reinforced with hybrid GFRP (glass fiber-reinforced polymer) bars and steel bars. Four beams were tested under fatigue loading, and the influence of effective reinforcement ratio and area ratio of FRP to steel bars ( A f /A s ) were studied. Residual strains in concrete and in reinforcement were investigated in the tests, and it was found that the residual strains in reinforcement cannot be neglected. An analytical model with residual strains considered is proposed to calculate the strain development in reinforcement bars and concrete under fatigue loading. The model without residual strains considered underestimates actual strains, especially under the lower limit of fatigue loading, and the model with residual strains considered fits well with the test results. Parametric analysis shows that fatigue life increases with the increase of effective reinforcement ratio, while the increase of area ratio of FRP to steel bars ( A f /A s ) reduces the fatigue life. And steel bars in members with higher A f /A s are subjected to higher stress under fatigue loading.